Stepwise management of asthma. Issue 1 (3rd September 2015) - Khalid, Ayesha N.
<x xml:space="preserve">Abstract</x> Background Stepwise management of asthma remains an area of evolving research. Asthma is one of the most expensive chronic diseases in the United States; stepwise management is an important area of focus, with several recent guidelines recommending management. Methods This is a review of published English language literature, focusing on management guidelines for asthma in adult and pediatric patients. Results Asthma is a chronic disease whose assessment of severity allows for therapeutic goals to match the impairment noted. Good evidence exists to aid risk reduction, leading to decreased emergency room visits, preventing loss of lung function in adults and lung growth in children, and optimizing pharmacotherapy with reduced side effects profile. Conclusion Recent asthma management guidelines incorporate 4 components of asthma care including: monitoring of severity, patient education, controlling external triggers, and medications, including recent attention to medication adherence. Asthma is an expensive chronic disease with preventive measures leading to reduced healthcare costs. Future targeted cytokine therapy to decrease serum and blood eosinophils may become an integral part of asthma management.